Experimental investigation of effects on performance, emissions and combustion parameters of biodiesel–diesel–butanol blends in a direct-injection CI engine. Issue 2 (17th February 2020) - Örs, İlker; Sarıkoç, Selçuk; Atabani, A.E.; Ünalan, Sebahattin
Abstract: This paper aims to asses and conduct a comparative analysis of fuel properties, performance, emissions and combustion characteristics of biodiesel produced from waste cooking oil (B100) as a cheap biodiesel feedstock, along with a binary blend of biodiesel–diesel (B20) and ternary blends of biodiesel–diesel–butanol as substitutions to diesel fuel. Although biodiesel and n-butanol have some negative impacts on engine performance parameters, they generally positively affect exhaust emission parameters compared to euro diesel. B100 caused an average reduction in brake power and exhaust gas temperature of 15.16% and 1.4%, respectively, although it increased brake specific fuel consumption on average by 14.09%, at full throttle under different engine load conditions. B100 decreased CO and HC emissions and smoke opacity by 65.4%, 61.07% and 54.94%, respectively. However, CO2 and NO emissions increased by 22.3% and 23.91%, respectively. Addition of n-butanol decreased some of the fuel thermo-physical properties such as density, viscosity and flash point. The average decreases in brake power when n-butanol was added were 6.17%, 7.49% and 11%, respectively, coupled with increases in specific fuel consumption of 6.25%, 8.96% and 14.29%, respectively. The addition of n-butanol decreased exhaust gas temperatures, CO, HC, NO and smoke emissions. Graphical Abstract: